Analysis of Utilization of the Silampari PGRI University Library as a Student Learning Resource - Marianita Marianita (Universitas Syiah Kuala, 2023)
The problem in this research is how to use the library at PGRI Silampari University for learning activities and self-development. In its use, the role of the library is not only used by students, but also by lecturers. The purpose of this study was to determine the analysis of the utilization of the PGRI Silampari University Library as a source of student learning. This research method is descriptive qualitative. This method discusses research based on field data or direct observation. To find out the level of usefulness of the PGRI Silampari University Library, the researcher described his research using various reference sources and interviews. The results of this study are the PGRI Silampari University library as a learning resource, that is, all groups, both lecturers and students, can use the library to support the learning system on the UNPARI Campus. Various references can provide valuable benefits both in learning and research. It is very clear that the library has various kinds of references that can support campus activities. The conclusion from this research is that the library as a reference source must be prioritized. Lecturers can invite students to visit the UNPARI library both to support materials and research.